Pharmacological blockade of cannabinoid type II receptors and mesenchymal stem cell transplantation in a model of peripheral neuropathic pain - A.-M. V. Yerofeyeva; S. V. Pinchuk; S. N. Rjabceva; A. Yu. Molchanova (Acta Biomedica Scientifica, 2024)
Objective. To evaluate the anti-nociceptive and reparative effects of adipose-derived mesenchymal stem cells (ADMSCs) under the pharmacological blockade of cannabinoid CB2 receptors in a model of peripheral neuropathic pain.Material and methods. In 40 male Wistar rats, modeling of peripheral neuropathy (NP) was performed by excising a sciatic nerve. On day 7 of the study, ADMSCs (1 × 106 cells/kg) were transplanted into the area of sciatic nerve injury without additional influences or after administration of the CB2 receptor antagonist AM630, as well as after incubation with AM630. Within 90  days, nociceptive sensitivity was studied, as well as a detailed analysis of gait using CatWalk XT (Noldus, Netherlands). On day 21 and day 90, histostructure of the distal segment of the sciatic nerve was assessed.Results. Pharmacological blockade of CB2 receptors both on the ADMSCs and in the soft tissues surrounding the site of sciatic nerve injury led to a decrease in withdrawal threshold and withdrawal latency from day 28 of the study compared with the group of rats with NP and transplantation of ADMSCs only. Local injection of AM630 before transplantation of ADMSCs contributed to the development of  NP-induced gait disturbances and increase of the number of damaged nerve fibers in the distal segment of sciatic nerve. Transplantation of ADMSCs pretreated with  AM630 did not significantly affect the rate of recovery of gait parameters, and decreased the number of damaged nerve fibers by day 90 of study.Conclusion. Blockade of CB2 receptors, both on the membranes of MSCs and in the area of damage to the peripheral nerve, has a negative effect on the development of the anti-nociceptive and reparative effects of MSCs.